Apoptotic Sphingolipid Ceramide in Cancer Therapy. (13th January 2011) - Huang, Wei-Ching; Chen, Chia-Ling; Lin, Yee-Shin; Lin, Chiou-Feng
Abstract : Apoptosis, also called programmed cell death, is physiologically and pathologically involved in cellular homeostasis. Escape of apoptotic signaling is a critical strategy commonly used for cancer tumorigenesis. Ceramide, a derivative of sphingolipid breakdown products, acts as second messenger for multiple extracellular stimuli including growth factors, chemical agents, and environmental stresses, such as hypoxia, and heat stress as well as irradiation. Also, ceramide acts as tumor-suppressor lipid because a variety of stress stimuli cause apoptosis by increasing intracellular ceramide to initiate apoptotic signaling. Defects on ceramide generation and sphingolipid metabolism are developed for cancer cell survival and cancer therapy resistance. Alternatively, targeting ceramide metabolism to correct these defects might provide opportunities to overcome cancer therapy resistance.